Crystalline Nanocellulose Anchored on Reduced Graphene Oxide for the Removal of Pharmaceuticals from Aqueous Systems: Adsorbent Characterization and Adsorption Performance. Issue 4 (26th January 2023) - Ogunleye, Deborah T.; Akpotu, Samson O.; Moodley, Brenda
Abstract: Improved adsorption of pharmaceuticals on reduced graphene oxide anchored on a crystalline nanocellulose base was achieved in this study. One‐pot synthesis of graphene‐nanocrystalline cellulose (G‐CNC) hybrid with in‐depth characterization was carried out, and the adsorbent's successful synthesis was confirmed through the characteristic peaks observed using FTIR and XRD. Further characterization was done using the surface area and porosity analyzer, TGA, SEM, TEM, and the elemental analyzer. The adsorbent was then applied in the adsorption of aspirin (Asp) and acetaminophen (Acet), which are frequently used over‐the‐counter anti‐inflammatory and antipyretic drugs. The major mechanism for the adsorption was ascertained to be through electrostatic interaction, hydrogen bonding, hydrophobic and π‐π interactions with the pharmaceutical. The maximum capacity for sorption obtained for the adsorption of Asp on graphene oxide (GO) and G‐CNC was 61.73 mg/g and 99 mg/g, respectively, while those of Acet on GO and G‐CNC were 20.41 mg/g and 76.34 mg/g, respectively. Abstract : Reduced graphene oxide with crystalline nanocellulose is a suitable adsorbent for the removal of aspirin and acetaminophen. The mechanism of adsorption is based on π‐π interactions, H‐bonding and electrostatic interactions.